Cross-Modal Interactions Between Auditory Attention and Oculomotor Control - Zhao, Sijia; Contadini-Wright, Claudia; Chait, Maria (The Journal of neuroscience, 2024)
Microsaccades are small, involuntary eye movements that occur during fixation. Their role is debated with recent hypotheses proposing a contribution to automatic scene sampling. Microsaccadic inhibition (MSI) refers to the abrupt suppression of microsaccades, typically evoked within 0.1 s after new stimulus onset. The functional significance and neural underpinnings of MSI are subjects of ongoing research. It has been suggested that MSI is a component of the brain's attentional re-orienting network which facilitates the allocation of attention to new environmental occurrences by reducing disruptions or shifts in gaze that could interfere with processing. The extent to which MSI is reflexive or influenced by top–down mechanisms remains debated. We developed a task that examines the impact of auditory top–down attention on MSI, allowing us to disentangle ocular dynamics from visual sensory processing. Participants ( N = 24 and 27; both sexes) listened to two simultaneous streams of tones and were instructed to attend to one stream while detecting specific task “targets.” We quantified MSI in response to occasional task-irrelevant events presented in both the attended and unattended streams (frequency steps in Experiment 1, omissions in Experiment 2). The results show that initial stages of MSI are not affected by auditory attention. However, later stages (∼0.25 s postevent onset), affecting the extent and duration of the inhibition, are enhanced for sounds in the attended stream compared to the unattended stream. These findings provide converging evidence for the reflexive nature of early MSI stages and robustly demonstrate the involvement of auditory attention in modulating the later stages.